Savings and Investment Patterns of Indonesian Society: An Analysis of Household Financial Behavior - Fatra Syahlan (Ilomata International Journal of Management, 2023)
The purpose of this study is to provide a comprehensive picture of financial behaviors in this dynamic socioeconomic context by examining the saving and investment habits of Indonesian households. Using a mixed-methods approach, the study combines quantitative survey data with qualitative material obtained through in-depth interviews. The demographic profile of the sample demonstrates a broad range of representation in terms of age groups, income levels, levels of education attained, and employment circumstances. Quantitative analyses reveal that a significant portion of participants save on a regular basis, with a variety of investment portfolios and savings vehicles that they prefer. Relationships between socioeconomic factors, such as education level and income, provide crucial information about what motivates people to make financial decisions. The findings demonstrate the important roles that behavioral variables, cultural influences, and risk perceptions all have in shaping household financial decisions. The study's conclusions, which highlight the need of targeted financial education programs and culturally sensitive interventions, can be helpful to policymakers, financial institutions, and educators alike. Overall, this study broadens our knowledge of household financial behavior and offers data that Indonesia can utilize to create policies that promote economic empowerment and financial resilience.